Onchocerciasis transmission in Ghana: persistence under different control strategies and the role of the simuliid vectors. - Poppy H L Lamberton; Robert A Cheke; Peter Winskill; Iñaki Tirados; Martin Walker; Mike Y Osei-Atweneboana; Nana-Kwadwo Biritwum; Anthony Tetteh-Kumah; Daniel A Boakye; Michael D Wilson; Rory J Post; María-Gloria Basañez (Public Library of Science (PLoS), 2015)
BACKGROUND:The World Health Organization (WHO) aims at eliminating onchocerciasis by 2020 in selected African countries. Current control focuses on community-directed treatment with ivermectin (CDTI). In Ghana, persistent transmission has been reported despite long-term control. We present spatial and temporal patterns of onchocerciasis transmission in relation to ivermectin treatment history. METHODOLOGY/PRINCIPAL FINDINGS:Host-seeking and ovipositing blackflies were collected from seven villages in four regions of Ghana with 3-24 years of CDTI at the time of sampling. A total of 16,443 flies was analysed for infection; 5,812 (35.3%) were dissected for parity (26.9% parous). Heads and thoraces of 12,196 flies were dissected for Onchocerca spp. and DNA from 11,122 abdomens was amplified using Onchocerca primers. A total of 463 larvae (0.03 larvae/fly) from 97 (0.6%) infected and 62 (0.4%) infective flies was recorded; 258 abdomens (2.3%) were positive for Onchocerca DNA. Infections (all were O. volvulus) were more likely to be detected in ovipositing flies. Transmission occurred, mostly in the wet season, at Gyankobaa and Bosomase, with transmission potentials of, respectively, 86 and 422 L3/person/month after 3 and 6 years of CDTI. The numbers of L3/1,000 parous flies at these villages were over 100 times the WHO threshold of one L3/1,000 for transmission control. Vector species influenced transmission parameters. At Asubende, the number of L3/1,000 ovipositing flies (1.4, 95% CI = 0-4) also just exceeded the threshold despite extensive vector control and 24 years of ivermectin distribution, but there were no infective larvae in host-seeking flies. CONCLUSIONS/SIGNIFICANCE:Despite repeated ivermectin treatment, evidence of O. volvulus transmission was documented in all seven villages and above the WHO threshold in two. Vector species influences transmission through biting and parous rates and vector competence, and should be included in transmission models. Oviposition traps could augment vector collector methods for monitoring and surveillance.